Microstructure and high-temperature mechanical properties of Nb-silicide based in-situ composites - 刘东明 姜荣丽 沙江波 (Transactions of Nonferrous Metals Society of China, 2006)
Nb-15W-18Si-xHf （x = 0, 5, 10 and 15, mole fraction, %） alloys were prepared by arc melting and then homogenized at 1 750 ℃ for 50 h. The microstructure and mechanical behaviors, such as Vickers hardness, fracture toughness, room- and hightemperature strength of the alloys were investigated. The microstructure of the annealed Nb-15W-18Si-xHf alloys is composed of large primary Nbss dendrite and fine eutectic mixture of Nbss and MsSi3 silicide. Both the hardness and the fracture toughness show an increase tendency at room temperature with increase of Hf content. The 0.2% compressive yield strength, σ0.2 of the alloys with 5 %Hf and 10%Hf are larger than 960 MPa at 1 200 ℃, and about 500 MPa even at 1 500 ℃.